Corrigendum: Periodontitis is associated with risk of conventional stent restenosis: Pilot case-control study - Osugue, Raphael [UNESP]; Castro dos Santos, Nidia C. [UNESP]; Araujo, Cassia F. [UNESP]; de Almeida, Flavio X.; Feres, Magda; Santamaria, Mauro P. [UNESP] (Frontiers, 2021)
In the original article, Magda Feres was incorrectly listed as the corresponding author. The correct corresponding author is Dr. Mauro Santamaria. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
Corrigendum: Periodontitis Is Associated With Risk of Conventional Stent Restenosis: Pilot Case-Control Study(Front. Dent. Med., (2021), 2, (673626), 10.3389/fdmed.2021.673626)
Keywords: atherosclerosis; cardiovascular disease; inflammation; periodontitis; stent restenosis